Piloting a Mathematics‐Writing Intervention with Late Elementary Students At‐Risk for Learning Difficulties. Issue 3 (10th June 2019) - Hebert, Michael A.; Bohaty, Janet; Roehling, Julia; Powell, Sarah R.
Abstract: High‐stakes mathematics assessments require students to write about mathematics, although research suggests students exhibit limited proficiency on such assessments. Students with LD may have difficulties with writing, mathematics, or both. Researchers employed an intervention for teaching students how to organize mathematics writing (MW). Researchers randomly assigned participants ( n = 61) in grades 3–5 to receive instruction in MW or information writing. Students receiving MW outperformed control students on a researcher‐developed measure of MW ( d = 1.05). Component assessment revealed MW students improved in writing organization ( d = 1.49) but not in mathematics content ( d = 0.11 ns ). Results also indicated MW students outperformed control on percentage of correct MW sequences ( d = 0.82). Future directions for MW intervention development are discussed.